(3JMUjd GdebUhO hfjd GdeQGe HPcQ HYV GdChGFd GdhGbYI aj GdGSdGe ef CUMGH GdfHi Ydjg GdUdGI hGdSdGes
(3ChdgG (B:s
(3GdMeO ddg GdPi aVdfG HNOeI GdYde GdTQja s
(3BNQgG (B:s
(3hgPG BNQ eG JjSQ LeYg ef PcQ HYV GdChGFd GdhGbYI ai GdGSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3eQJH Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B94 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI OGQ GdNWjH HGdbOS s
Keywords: (3GdJGQjNs